Fractional Hardy-Sobolev elliptic problems - Yang, Jianfu; Yu, Xiaohui (Topological Methods in Nonlinear Analysis, 2020)
In this paper, we study the following singular nonlinear elliptic problem \begin{equation} \begin{cases} \displaystyle (-\Delta)^{ \alpha/ 2} u=\lambda |u|^{r-2}u+\mu\frac{|u|^{q-2}u}{|x|^{s}} &\text{in }\Omega, \\ u=0 &\text{on } \partial\Omega, \end{cases} \tag{P} \end{equation} where $\Omega$ is a smooth bounded domain in $\mathbb R^N(N\geq 2)$ with $0\in \Omega$, $\lambda,\mu> 0$, $0< s\leq\alpha$, $(-\Delta)^{\alpha/ 2}$ is the spectral fractional Laplacian operator with $0< \alpha< 2$. We establish existence results and nonexistence results of problem \eqref{eq:1} for subcritical, Sobolev critical and Hardy-Sobolev critical cases.